Analisis Yuridis Kejahatan Pembalakan Liar Di Kota Batam berdasarkan Undang-Undang Nomor 18 Tahun 2013 tentang Pencegahan dan Pemberantasan Pengrusakan Hutan - Victor Marsongkhoe; Tantimin Tantimin (Fakultas Hukum, Universitas Internasional Batam, 2020)
Forests are one of the oxygen-producers on Earth and a place to live various types of plants and animals. The existence of forests on Earth is very important since its absence will have fatal consequences for all life. One of the effects due to the reduction in the number of forests is global warming, flooding, landslides, reduced supply of oxygen, landslides, and so forth. The city of Batam has experienced a reduction in the number of forested areas each year due to various factors, one of which is the emergence of illegal logging crimes in Batam City. This study uses a qualitative Empirical research method by conducting interviews and collecting data from resource persons.The survei method is done by distributing questionnaires as supporting data. Respondents sampeld were Batam University Students, and Batam City Communities. Data testing is done by correlating the results of interviews received with data obtained, which is then correlated with legal theory that aims to draw conclusions about the effectiveness ofUndang-Undang Nomor 18 Tahun 2013 in Batam City. The results of this study provide information on the effectiveness of Undang-Undang Nomor 18 Tahun 2013 in Batam City and provide information on the factors that cause the emergence of illegal logging crimes and obstacles that law enforcement might face in dealing with them. This information is expected to help law enforcement regarding crime of illegal logging in the city of Batam.